Antimicrobial action of four herbal plants over mixed-species biofilms of Candida albicans with four different microorganisms - Domingues, Nádia [UNESP]; Ramos, Lucas de Paula [UNESP]; Pereira, Larissa Marques [UNESP]; do Rosário Estevam dos Santos, Pâmela Beatriz [UNESP]; Scorzoni, Liliana [UNESP]; Pereira, Thaís Cristine [UNESP]; Abu Hasna, Amjad [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP]; de Oliveira, Luciane Dias [UNESP] (Wiley, 2022)
This study aimed to evaluate the antimicrobial effect of four herbal plants glycolic extracts over mixed-species biofilm composed of Candida albicans (C. albicans) and another pathogenic bacterium as alternative therapy to be investigated. Four plants extract of Pfaffia paniculata roots; Hamamelis virginiana leaf, Stryphnodendron barbatiman tree bark and Gymnema sylvestre stem and leaves were tested over multi-species biofilm of C. albicans (ATCC 18804) and Streptococcus mutans (ATCC 35688), Staphylococcus aureus (ATCC 6538), Enterococcus faecalis (ATCC 4083) or Pseudomonas aeruginosa (ATCC 15442) for 5 min and 24 h and colony forming units per millilitre was calculated. The data were analysed using Kruskal–Wallis with Dunn's test (p ≤ 0.05). All tested extracts showed antimicrobial action over the mixed-species biofilms after 24 h. Some extracts eliminated totally the biofilms. The glycolic extract of P. paniculata, H. virginiana, S. barbatiman and G. sylvestre are effective over mixed-species biofilms and may be indicated as endodontic irrigant or intracanal medication.
Keywords: biofilm: Candida albicans; Enterococcus faecalis; Pseudomonas aeruginosa; Staphylococcus aureus; Streptococcus mutans